Common sage (Salvia officinalis) antiviral role: potentiality of a Unani hand sanitizer in COVID-19 (corona virus) second wave control - Azad, MA Momith; Mahmud, Abdullah Al; Islam, Md Shahidul; Gouhar, Ahmed Iqbal (Asian Journal of Medical and Biological Research, 2021)
The world has been fighting against a pandemic for more than a year, caused by a highly infectious disease named COVID-19 rooted by the novel coronavirus 2019. It has already been spread out in most of the countries and a few of which are experiencing second wave. The Novel coronavirus-2019 (SARS CoV-2) incurred more than 1.6 million deaths and 76 million cases in the world population (till 20 December 2020). Although some vaccines are being launched, however, their effectivity and availability are still unknown. Maintaining personal hygiene and social distance are the best way of protection. Hand washing is the utmost recommendation for the maintenance of personal hygiene since hands can be contaminated by the droplets easily. Particularly, in pandemic situations, it is crucial to interrupt the transmission chain of the virus by the practice of proper hand sanitization. The hand sanitization solely depends on the use of effective hand disinfecting agents. Natural formula-based disinfectants can be preferable to chemicals because of higher efficacy and lower adverse effects. Unani medicine is the system based on natural formulations. „Raihan‟ (common sage, Salvia officinalis) is frequently used in Unani medicine for its higher disinfectant role. Common sage extract with ethanol may provide superior efficacy against COVID-19. In this article, we presented information on common sage and its potentiality using with ethanol as a natural, skin-friendly hand sanitizer to prevent harmful action of chemical mixing synthetic sanitizer. Asian J. Med. Biol. Res. December 2020, 6(4): 611-617